2018
DOI: 10.1111/myc.12866
|View full text |Cite
|
Sign up to set email alerts
|

DCSIGN and VDR polymorphisms are associated with chronic form of paracoccidioidomycosis with oral manifestations

Abstract: Paracoccidioidomycosis (PCM) is a granulomatous disease caused by fungi of the species complex of the Paracoccidioides genus. One of the main clinical manifestations of PCM is the presence of oral lesions with the presence of epithelioid granulomas. In this work, we aimed to evaluate the frequency of SNPs in the TNF-α, JAK1, VDR, DC-SIGN and FcγRIIa genes in patients with chronic PCM and verify possible association of these SNPs with the organisation pattern of the granulomas in the oral lesions. A total of 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The heterogeneity test suggested that our final results were robust and unaffected by other factors. Additionally, due to the strong LD between VDR rs7975232 and rs2239185, haplotype analysis was further conducted with the results suggested that SNP-SNP interactions in the VDR gene increased susceptibility to OLP, which further validated the single-gene analysis results [23,24,25].…”
Section: Discussionmentioning
confidence: 71%
“…The heterogeneity test suggested that our final results were robust and unaffected by other factors. Additionally, due to the strong LD between VDR rs7975232 and rs2239185, haplotype analysis was further conducted with the results suggested that SNP-SNP interactions in the VDR gene increased susceptibility to OLP, which further validated the single-gene analysis results [23,24,25].…”
Section: Discussionmentioning
confidence: 71%
“…The heterogeneity test suggested that our final results were robust and unaffected by other factors. Additionally, due to the strong LD between VDR rs7975232 and rs2239185, haplotype analysis was further conducted with the results suggested that SNP-SNP interactions in the VDR gene increased susceptibility to OLP, which further validated the single-gene analysis results [21][22][23].…”
Section: Discussionmentioning
confidence: 76%
“…Our study found the association between the genetic variation of VDR and OLP susceptibility .The results revealed that mutations in VDR rs2239185 and rs7975232 increased the risk of OLP, and OLP risk increased with increasing adverse alleles. The heterogeneity test suggested our results were not heterogeneous in different populations, which confirmed that our final results were robust and unaffected by other factors.Additionally, due to the strong LD between VDR rs7975232 and rs2239185, further haplotype analysis was conducted with the results suggested that SNP-SNP interactions in the VDR gene increased susceptibility to OLP, which further validated the single-gene analysis results[23, 24,25].. .…”
mentioning
confidence: 65%